Pengembangan Media Question Card Pada Materi Sejarah Kesultanan Aceh Darussalam Untuk Siswa Kelas X IPS SMA NEGERI 13 Padang - Tistiarni Tistiarni; Hera Hastuti (Jurusan Sejarah FIS UNP, 2021)
The background of this research is the low level of students' causality thinking ability. Students do not understand how a historical event occurs and what the consequences are. This is based on the findings and observations of researchers when carrying out educational field practice at SMAN 13 Padang in the January-June 2020 semester, these findings state that the ability of students to analyze cause and effect is only in a small proportion of students, namely students who have the ability high, while others have not. Students only rely on information from the teacher, they are lazy to read history books. To train and foster students' causality thinking skills, a media that can help is needed, namely the question card media. Media Question Card is a learning media in the form of paper cards containing questions with pictures about the material to be taught. The research method is R&D or Research and Development, the purpose of R&D is to produce products in the form of historical learning media. The results showed that the question card media proved feasible to be applied in high school with data validation tests from causality analysis experts and media experts of 3.5 and 3 validation tests from teachers of 3.5 based on the results of the validation test, it can be concluded that the question card media is feasible. used in history learning. Keywords: Question Card Media, Historical Learning, Causality Thinking